Sistem Smart Parking Terdistribusi dengan Menggunakan Mobile Cloud Computing - Arfan, M; Sumardi, Sumardi; Riyadi, Munawar Agus (JTET (Jurnal Teknik Elektro Terapan), 2017)
The availability of parking space for urban areas is very limited. Parking lots in office complexes and community centers are still not able to accommodate the number of motor vehicles that increase each year. According data from the Central Bureau of Statistics, the number of motor vehicles has reached 129.2 million units by 2016. This has not been supported by parking managers ability to compensate for the growing number of vehicles using parking services. Some parking managers have been using the computer as a means of parking management support. The computer functions as an incoming data logging machine, a parking rate payment system and a security control of the document. On the other hand, information about the availability of parking lots is needed by parking service users. The data provided by the parking operator has not been able to provide information on the density of the parking lot in several parking locations in one area. From the problem, it is necessary to build a smart parking system that can provide information density of several parking locations. The data on the parking register engine can be processed into parking information on mobile cloud devices then provide the shortest route recommendations using the Dijkstra algorithm. With mobile computing technology, parking lava availability information will take place in real-time. Identification of capacity and density of each parking space is realized in the form of mobile cloud-based applications.Keywords : mobile computing, cloud computing, smart parking, Dijkstra